The detection of hot cores and complex organic molecules in the Large Magellanic Cloud - Sewiło, Marta; Ward, Jacob L. (Arxiv, 2018)
We report the first extragalactic detection of the complex organic molecules (COMs) dimethyl ether (CH$_3$OCH$_3$) and methyl formate (CH$_3$OCHO) with the Atacama Large Millimeter/submillimeter Array (ALMA). These COMs together with their parent species methanol (CH$_3$OH), were detected toward two 1.3 mm continuum sources in the N 113 star-forming region in the low-metallicity Large Magellanic Cloud (LMC). Rotational temperatures ($T_{\rm rot}\sim130$ K) and total column densities ($N_{\rm rot}\sim10^{16}$ cm$^{-2}$) have been calculated for each source based on multiple transitions of CH$_3$OH. We present the ALMA molecular emission maps for COMs and measured abundances for all detected species. The physical and chemical properties of two sources with COMs detection, and the association with H$_